2021
DOI: 10.1371/journal.pone.0258497
|View full text |Cite
|
Sign up to set email alerts
|

CCRK/CDK20 regulates ciliary retrograde protein trafficking via interacting with BROMI/TBC1D32

Abstract: CCRK/CDK20 was reported to interact with BROMI/TBC1D32 and regulate ciliary Hedgehog signaling. In various organisms, mutations in the orthologs of CCRK and those of the kinase ICK/CILK1, which is phosphorylated by CCRK, are known to result in cilia elongation. Furthermore, we recently showed that ICK regulates retrograde ciliary protein trafficking and/or the turnaround event at the ciliary tips, and that its mutations result in the elimination of intraflagellar transport (IFT) proteins that have overaccumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(45 citation statements)
references
References 92 publications
14
31
0
Order By: Relevance
“…Consistent with the role of ICK downstream of CCRK, mutations of ICK and CCRK homologues in various organisms cause a long cilia/flagella phenotype and often increase the variation in the ciliary length of individual cells (Asleson and Lefebvre, 1998;Berman et al, 2003;Bengs et al, 2005;Burghoorn et al, 2007;Tam et al, 2007;Omori et al, 2010;Yang et al, 2013;Moon et al, 2014;Okamoto et al, 2017;Yi et al, 2018;Jiang et al, 2019;Maurya et al, 2019;Wang et al, 2019;Nakamura et al, 2020). Furthermore, mutations of CCRK and BROMI (also known as TBC1D32), which interact with CCRK (Ko et al, 2010;Noguchi et al, 2021), in humans cause ciliopathies, and CCRK and BROMI mutant mice demonstrate defects in embryonic development caused by aberrant Hh signaling (Ko et al, 2010;Adly et al, 2014;Snouffer et al, 2017;Wang et al, 2018;Alsahan and Alkuraya, 2020;Hietamäki et al, 2020). We have recently shown that not only in ICKknockout (KO) cells but also in CCRK-KO cells derived from human telomerase reverse transcriptase-immortalized retinal pigment epithelial 1 (hTERT-RPE1) cells, the average ciliary length is longer and the variation in ciliary length is larger than in control RPE1 cells, and that excessively accumulated proteins at the bulged ciliary tips of these KO cells are eliminated via extracellular vesicles (ECVs) (Noguchi et al, 2021).…”
Section: Introductionmentioning
confidence: 86%
“…Consistent with the role of ICK downstream of CCRK, mutations of ICK and CCRK homologues in various organisms cause a long cilia/flagella phenotype and often increase the variation in the ciliary length of individual cells (Asleson and Lefebvre, 1998;Berman et al, 2003;Bengs et al, 2005;Burghoorn et al, 2007;Tam et al, 2007;Omori et al, 2010;Yang et al, 2013;Moon et al, 2014;Okamoto et al, 2017;Yi et al, 2018;Jiang et al, 2019;Maurya et al, 2019;Wang et al, 2019;Nakamura et al, 2020). Furthermore, mutations of CCRK and BROMI (also known as TBC1D32), which interact with CCRK (Ko et al, 2010;Noguchi et al, 2021), in humans cause ciliopathies, and CCRK and BROMI mutant mice demonstrate defects in embryonic development caused by aberrant Hh signaling (Ko et al, 2010;Adly et al, 2014;Snouffer et al, 2017;Wang et al, 2018;Alsahan and Alkuraya, 2020;Hietamäki et al, 2020). We have recently shown that not only in ICKknockout (KO) cells but also in CCRK-KO cells derived from human telomerase reverse transcriptase-immortalized retinal pigment epithelial 1 (hTERT-RPE1) cells, the average ciliary length is longer and the variation in ciliary length is larger than in control RPE1 cells, and that excessively accumulated proteins at the bulged ciliary tips of these KO cells are eliminated via extracellular vesicles (ECVs) (Noguchi et al, 2021).…”
Section: Introductionmentioning
confidence: 86%
“…CDK20) [ 159 ]. This kinase was shown to be involved in cancer, cancer metastatic suppression, hedgehog signaling and IFT regulation [ 183 , 184 , 185 , 186 ]. Here we focus on the effect of CCRK and its homologs (LF2 in Chlamydomonas , DYF-18 in C. elegans , Table 1 ) have on IFT.…”
Section: Ift Regulation From the Perspective Of Regulatory Proteinsmentioning
confidence: 99%
“…Here we focus on the effect of CCRK and its homologs (LF2 in Chlamydomonas , DYF-18 in C. elegans , Table 1 ) have on IFT. Knockout mutants of CCRK in mammals, Chlamydomonas and C. elegans have longer cilia with more length variability [ 160 , 161 , 175 , 186 ]. Furthermore, in mammalian cilia, accumulations of IFT components and shedding of vesicles from the tip have been observed [ 185 , 186 ].…”
Section: Ift Regulation From the Perspective Of Regulatory Proteinsmentioning
confidence: 99%
See 2 more Smart Citations